Efektivitas dan Hambatan Yang Timbul dari Penegakan Konvensi Apostille di Indonesia - Najma Fauziyah Rabbani; Elan Jaelani (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2024)
Research on "EFFECTIVENESS OF ENFORCING ACCESS TO THE APOSTILLE CONVENTION AND OBSTACLES THAT WILL BE FACED IN INDONESIA" is research using normative juridical methods which focuses on the study of positive legal rules which uses an approach to existing legislation and conventions and focuses on reviewing legal studies. The Apostille Convention was originally born and ratified in The Hague, Netherlands on October 5 1961 as an international agreement which aims to eliminate several requirements related to the legalization of diplomatic or foreign public documents. The Apostille Convention came into force on January 21 1965. The effectiveness of Apostille enforcement in Indonesia includes making it easier for the public to legalize a foreign public document, improving a more reliable legal system, simplifying administrative costs and also supporting economic activities. The obstacle to enforcing the Apostille is that it adds challenges and responsibilities for notaries. In the process, the issuance of the apostille certificate creates new problems for the notary and adds responsibility, because the issue of the certificate requires the notary to maintain the confidentiality of the contents of the authentic deed in accordance with the UUJN (Notary Public Law), but in the Apostille, the notary is required to upload data to Kemenkumham website which will then be verified by the authorities. This will then lead to the leak of confidential information and conflict with UUJN.